SHRIMP dating and nd isotope geology of the archean terranes of the uweinat-kamil inlier, egypt-sudan-libya - Bea, F.; Montero, P.; Anbar, M.; Talavera, Cristina (Elsevier BV, 2011)
The Precambrian terranes of north east Africa are still poorly known. It is generally believed that the oldest rocks in the region are the charnockitic gneisses of the Uweinat massif, located at the triple junction between Libya-Egypt-Sudan, because they have yielded Rb-Sr ages around 2.6Ga and Nd TDM model ages around 3.0-3.2Ga. Here we confirm that these rocks are indeed Archean with SHRIMP U-Pb zircon ages as old as 3.0Ga, but we also report older rocks to the east, in the neighboring Gebel Kamil region. This area contains a metaigneous complex formed of tonalite-trondhjemite-granite (TTG) and gabbro-diorite (GbD) gneisses with a whole-rock Sm-Nd isochron age of 3.16±0.16Ga, average Nd TCR of 3.17±0.04Ga, and average eopenNd(3.2Ga) of 3.4±0.3. The oldest TTG gneisses, which are also the oldest rocks found to date in north east Africa, contain large magmatic zircons with SHRIMP U-Pb crystallization ages peaking at 3.22±0.04Ga, closely matching the Sm-Nd and the Nd TCR model ages. These ages are interpreted to represent arc-magmas produced between 3.1Ga and 3.3Ga. Other TTGs have younger Archean zircon ages that form a continuum between 3.1Ga and 2.55Ga, with three peaks at around 2.97Ga, 2.85Ga, and 2.6-2.7Ga; these rocks were apparently generated from the older TTGs during repeated events of crustal recycling. The crust was stable from 2.55Ga to 2.0Ga, when an intense thermal event generated rims of variable thickness over the Archean zircons. Neither the reworking from 3.1Ga to 2.55Ga, nor the metamorphism at 2.0Ga involved the addition of juvenile material to the crust of this area, which behaved as an almost closed system from 3.1Ga to 0.75Ga, when the intrusion of Pan-African I-type granitoids with a juvenile component began. © 2011 Elsevier B.V.